2014
DOI: 10.1111/tan.12355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the HLA characteristics of Italian patients on donor search outcome in unrelated hematopoietic stem cell transplantation

Abstract: The information regarding the probability of finding a matched unrelated donor (MUD) within a relatively short time is crucial for the success of hematopoietic stem cell transplantation (HSCT), particularly in patients with malignancies. In this study, we retrospectively analyzed 315 Italian patients who started a search for a MUD, in order to assess the distribution of human leukocyte antigen (HLA) alleles and haplotypes in this population of patients and to evaluate the probability of finding a donor. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…A similar observation was reported by Testi et al, 27 who identified a 9/10-or 10/10-matched donor for 75% of their 315 patients, who had a high frequency allele. In contrast Grubic et al 28 reported having found a 9/10-or 10/10-matched donor for 95% of 105 Croatian patients, but their cohort only consisted of patients who were actually transplanted.…”
Section: Discussionsupporting
confidence: 67%
“…A similar observation was reported by Testi et al, 27 who identified a 9/10-or 10/10-matched donor for 75% of their 315 patients, who had a high frequency allele. In contrast Grubic et al 28 reported having found a 9/10-or 10/10-matched donor for 95% of 105 Croatian patients, but their cohort only consisted of patients who were actually transplanted.…”
Section: Discussionsupporting
confidence: 67%
“…44), and enter into ER as NH 2 terminal-extended precursors that are trimmed before assembly with MHC-I molecules (26,29,37). The MHC-I consensus motif with a proline at position 2 accounts for mouse L d and more than 33% and 36% of all known human HLA-B and HLA-C motifs in the Italian population (45). Thus, one third of individuals carrying these HLA class I alleles will react with reduced surface expression upon ERAP1 inhibition.…”
Section: Cd56mentioning
confidence: 99%
“…Like MHC class I, TAP prefers peptides with hydrophobic or basic residues at the carboxy ends, and transports peptides with proline at position 2 inefficiently . However, since over 33% and 36% of all known human leukocyte antigen (HLA)‐B and HLA‐C alleles in the Caucasian population bind peptides with proline in position 2 (Table ) , it is plausible that these epitopes gain access to the ER as longer precursors with additional N‐terminal flanking residues that will be removed before assembly with HLA class I molecules. Consistent with this hypothesis, ERAP1 and ERAP2 poorly trim proline residue at position 2 causing an accumulation of peptides with these characteristics .…”
Section: Mhc Class I Antigen‐processing Pathway: a Finely Coordinatedmentioning
confidence: 65%